EVALUASI PENYEDIAAN SARANA DAN PRASARANA DI PERUMAHAN PURI DINAR MAS SEMARANG - Tiasa Adimagistra; Bitta Pigawati (Diponegoro University, 2016)
Community needs for settlement area, especially in the city of Semarang increase rapidly, so the government in 2005 make a program called 100,000 RSS (Simple Healthy House) to meet those needs. RSS is a settlement with facilities and infrastructure that are inadequate. The construction of facilities and infrastructure of the settlement should refer to the SNI 03-1733-2004 on Procedures for Environmental Planning in Urban Housing. The research objective is to evaluate the facilities and infrastructure based on ISO and user perception in Puri Dinar Mas Semarang. The method which used to analyze are the quantitative descriptive and comparative methods. The descriptive quantitative method is used to identify the availability and existing condition with the user's perception of the infrastructure Puri Dinar Mas, while the comparative descriptive method is used to compare the existing condition with SNI and comparing the user's perception of the condition of housing infrastructure based on the observation. There is a 61% infrastructure is available based on SNI and 70% in good condition. Based on the results of the comparison with SNI only 32% meet the standard. The results of the perception of users 80% are stated that the condition of facilities and infrastructure that exist in this housing is good, meanwhile the comparison of existing condition with the perception of users found that 84% is good, 8% is bad, and the remaining 8% is moderate.